Recurrent anterior dislocation of radial head treated with ulnar distraction osteotomy and reconstruction of annular ligament using palmaris longus tendon with bioabsorbable screw anchoring: A case report - Winanto, Iman Dwi; Siregar, Alamsyah Faritz; Nugraha, Tesar Akbar (Jurnal Prima Medika Sains, 2024)
Introduction: Radial head dislocation in children may be either congenital, an isolated injury or more commonly part of a complex injury to the elbow. Isolated traumatic radial head dislocation in children is a rare and easily missed condition.The reported case shows various treatment and intervention with ulnar osteotomy and annular ligament reconstruction in order to reach the definitive reduction of recurrent dislocation of radial head. Case Presentation: Male 9 years old with anterior dislocation of the radial head, came with difficulty on flexing his elbow due to bony prominence on his anterior elbow. He had recurrent radial head dislocation with redundant annular ligament. From the physical examination there was a prominent radial head on anterior region of elbow. From x-ray examination we found anterior dislocation of ulnar head without any fracture or deformity of ulna. Patient underwent ulnar distraction osteotomy to achieve radial traction and allow stable reduction of radial head. After 5 months he had reconstruction of annular ligament with palmaris longus tendon graft and anchoring with bioabsorbable screw in order to reduce and stabilize the radial head. Conclusion: In this case we found ulnar osteotomy may gave improvement for the reduction of the radial head. But additional annular ligament reconstruction give stability of the radial head which will held in place with full range of motion of the elbow. So this combined procedures hopefully can gave best achievement and satisfactory results of the children and last a lifetime.